2016
DOI: 10.1007/jhep09(2016)091
|View full text |Cite
|
Sign up to set email alerts
|

Two-loop master integrals for the mixed EW-QCD virtual corrections to Drell-Yan scattering

Abstract: We present the calculation of the master integrals needed for the two-loop QCD×EW corrections to q +q → l − + l + and q +q → l − + ν , for massless external particles. We treat the W and Z bosons as degenerate in mass. We identify three types of diagrams, according to the presence of massive internal lines: the no-mass type, the onemass type, and the two-mass type, where all massive propagators, when occurring, contain the same mass value. We find a basis of 49 master integrals and evaluate them with the metho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(109 citation statements)
references
References 153 publications
(200 reference statements)
2
107
0
Order By: Relevance
“…Mixed QCD-QED virtual correction to lepton-pair production have been presented in [87], while the full set of Master Integrals relevant for the evaluation of the complete set of QCD-EW virtual corrections has been presented in ref. [88]. The doublereal contribution to the total cross section for the on-shell single gauge boson production has been presented in ref.…”
Section: Mixed Qcd-ew Correctionsmentioning
confidence: 99%
“…Mixed QCD-QED virtual correction to lepton-pair production have been presented in [87], while the full set of Master Integrals relevant for the evaluation of the complete set of QCD-EW virtual corrections has been presented in ref. [88]. The doublereal contribution to the total cross section for the on-shell single gauge boson production has been presented in ref.…”
Section: Mixed Qcd-ew Correctionsmentioning
confidence: 99%
“…is not yet available, although first steps in this direction have been taken by calculating two-loop contributions [77][78][79][80][81], the full O(αα s ) correction to the W/Z-decay widths [82,83], and the full O(α) EW corrections to W/Z+jet production including the W/Z decays [39,40,84].…”
Section: Towards Exact O(αα S ): Assessment Of the Accuracy Of Currenmentioning
confidence: 99%
“…systems with an associated matrix where the dependence on the space-time dimensions is decoupled from the kinematics [8,9], has led to a substantial improvement of the system-solving strategy [10][11][12][13][14][15][16][17][18][19], and to the availability of many novel results. In the case of Feynman integrals that depend on several scales, we have shown that the Magnus exponential [11] is an efficient tool to derive MIs obeying canonical systems starting from a basis of MIs that obey systems of DEs whose matrix has a linear dependence on the space-time dimension [20][21][22].…”
Section: Jhep04(2017)008mentioning
confidence: 99%